PELAKSANAAN TUGAS DAN FUNGSI SATUAN BAKTI PEKERJA SOSIAL DALAM PENANGANAN PERMASALAHAN ANAK TERLANTAR DI KOTA KUPANG - Fafo, Yuvani; Tuan, Yohanes; Nuban, Detji K. E. R. (Petitum Law Journal, 2024)
Abandoned children are children whose needs are not met in a reasonable manner, whether physical, mental, spiritual or social in accordance with what is regulated in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection in Article 1 number 6 The aim of this research is to understand the implementation, functions and obstacles of the Social Worker Service Unit in handling the problem of abandoned children in Kupang City. The research method used is empirical research, namely through interviews, then the data is analyzed descriptively qualitatively. The research results show: (1) The duties of social workers can be carried out well by professional officers in accordance with Law Number 14 of 2019 concerning Social Workers. (2) Internal barriers, namely parental education and parents not understanding about children. Meanwhile, external obstacles include the scope of children's problems, coordination between SKPD, combining children's cases with other cases, lack of social worker service personnel and facilities for outreach to children. The researchers' conclusions are: (1) The implementation of duties and functions by the social worker service unit as liaison, educator, facilitator, mediator, counselor, through mentoring, counseling and family support has been carried out well by the social worker service unit. (2) The obstacles faced in carrying out the duties and functions of the social work service unit are internal obstacles and external obstacles. It is hoped that the government, especially social services, can carry out monthly monitoring of parents so that the funds distributed are used properly for children's needs and provide outreach to parents.